Spatial and temporal distances in a virtual global world: Lessons from the COVID-19 pandemic - Nachum, Lilac; Buckley, Peter J. (Journal of International Business Studies, 2023)
The experience of COVID-19 prompted us to rethink the imperatives of distance for the organization of value-creating activities globally. We advance a conceptualization of distance as representing separation in both space and time and posit that these distance dimensions represent different kinds of separation and require varied theoretical attention. We delineate the intrinsic qualities of spatial and temporal distances and theorize the impact of this extended conceptualization of distance on major tenets of international business theory and their predictions regarding the patterns of international business activity. We illustrate the ways by which varying configurations of spatial and temporal distances serve different value-creating activities and draw their implications for countries' global integration. We advance a call for more attention to time and temporal distance and their impact on the ways firms organize their value-creating activities in an increasingly virtual world.